Implementasi Pembelajaran Pendidikan Agama Islam Dalam Membentuk Karakter Edupreneur - Rachmadonna Retno A.F.A; Laila Badriyah; Eli Masnawati (LP3M IAI Al Urwatul Wutsqo Jombang, 2025)
This study examines the implementation of Islamic Religious Education (PAI) learning in shaping edupreneur character at Wachid Hasyim 2 Taman Sidoarjo High School. The purpose of the study was to analyze how PAI learning can be integrated with entrepreneurship education to form a noble edupreneur character. The research method uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects included PKWU teachers and students of class XI-F7. The results showed that the implementation of PAI learning in shaping edupreneur character has been successfully implemented by using the exemplary approach of the Prophet Muhammad as a noble trader. The edupreneur program, integrated with Islamic values, proved effective in building student independence through learning that combines theory and practice of entrepreneurship. Supporting factors include student creativity, the application of Islamic business ethics, and school support. The inhibiting factors include students' limited managerial skills and the lack of competent human resources. The research conclusion shows that the integration of PAI learning with entrepreneurship education can be an effective model for preparing a generation with strong character and independence in creating jobs.